Studi Komparatif Pelaksanaan Meditasi di Sekolah Berbasis Buddhis di Banten pada Pembelajaran Tatap Muka dan Jarak Jauh - Purnomo Ratna Paramita (STABN Sriwjaya, 2023)
This study aims to obtain an overview of the implementation of meditation in Buddhist-based schools in Banten during face-to-face and distance learning. The Buddhist-based schools in Banten consist of: Dharma Putra School, Ariya Metta School, Jaya Manggala School, Bodhisatta School, Atisa Dipamkara School, Punna Karya School, Buddhist College School, Dharma Widya School, and Ehipassiko School. This research focuses on implementation, timing, types and constraints that arise. This study uses a comparative descriptive qualitative method with data collection techniques through interviews and document studies, then the data is analyzed using the Miles, Huberman Saldana technique. The results showed that 8 out of 9 Buddhist-based schools in Banten continued to apply meditation as a PPK program during distance learning. There is a decrease in the number of meditation practices in 1 week during distance learning by 77.37%. 7 out of 9 Buddhist-based schools in Banten changed the type of meditation applied to distance learning. Obstacles that often arise in the implementation of online meditation are signals, internet data quotas, devices and environmental noise disturbances.